Sequential Cleavage of Lignin Systems by Nitrogen Monoxide and Hydrazine - Hofmann, Laura; Hofmann, Dagmar; Prusko, Lea; Altmann, Lisa-Marie; Heinrich, Markus (dvanced Synthesis & Catalysis, 2020)
The cleavage of representative lignin systems has been achieved in a metal-free two-step sequence first employing nitrogen monoxide for oxidation followed by hydrazine for reductive C−O bond scission. In combining nitrogen monoxide and lignin, the newly developed valorization strategy shows the particular feature of starting from two waste materials, and it further exploits the attractive conditions of a Wolff-Kishner reduction for C−O bond cleavage for the first time. (Figure presented.).
CRIS-Team Scopus Importer:2020-03-31
Keywords: Depolymerization; Hydrazine; Lignin; Nitrogen oxides; Pyrazole